Analisis Faktor - Faktor Yang Mempengaruhi Minat Mahasiswa Akuntansi Untuk Berkarir Menjadi Akuntan Berpraktik: Studi Kasus Mahasiswa Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram - Nurqomariatun; Sasanti, Elin Erlina; Isnaini, Zuhrotul (Fakultas Ekonomi dan Bisnis Unram, 2025)
This study aims to examine the influence of the perception of accounting students at the Faculty of Economics and Business, University of Mataram on the interest in becoming a practicing accountant. The variables used in this study are job market considerations, self-efficacy, and subjective norms. The sample in this study was determined using purposive sampling techniques and questionnaire distribution with a total of 67 respondents. Statistical data analysis uses multiple regression analysis techniques using the SPSS version 25 application. The results of this study show that the variables of job market considerations, self-efficacy, and subjective norms have a positive and significant effect on the interest in becoming a practicing accountant.